AN EXILIC MEDITATION: OVID'S ARACHNE AS ARTISTIC REBELLION, POLITICAL ALLEGORY, AND PERSONAL ALLUSION. - Dalbock, Abigail (Akroterion, 2024)
This article examines Ovid's depiction of the Arachne myth in the Metamorphoses (6:1-145). Within the context of Augustan Rome, it explores the intricate dynamics of power, artistic autonomy, and the interplay between divine intervention and human agency in relation to the Arachne narrative. Moreover, it positions the narrative against the backdrop of Ovid's own literary career and exile. Thus, through a close reading of the text and an analysis of intertextual references to Ovid's earlier works, it suggests that the Arachne narrative may have undergone revision sometime after Ovid's relegation sentence was handed down and, as such, reflects his own encounters with imperial authority and censorship.